A systematic review on the most common injuries in handball - Gîtman Roxana-Maria; Breha Alexandru Mihai; Mihăilă Ion; Iconaru Ioana; Popescu Corina; Ciucurel Constantin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
High performance in sports requires lots of training and a good knowledge of training techniques, characteristics of physical training, mechanisms of lesion occurrence and methods of prevention sports pathology. Handball specific requirements are very important in order to avoid specific trauma, and in this matter specific literature is very important for specialists. This paper aimed to find how many relevant papers were published from 2018 to present regarding handball injuries and prevention of handball injuries, in two databases, PUBMED and Library Genesis (libgen.li.). For this matter there were used three equations to find results in the two databases selected, and for each of them there were quantified the number of scientific papers that were relevant to this study. Also, in this paper we presented inclusion/exclusion criteria, the results we found, and also, the analysis of each paper's quality, for the papers that were a match to the inclusion criteria. For each paper we evaluated the quality of content using 5 relevant questions that help us understand the missing aspects that need further study, being applied individually for the two databases. The results we found revealed a very poor literature regarding injuries in handball and also prevention of injury in handball.